2003
DOI: 10.1097/01.hdx.0000050417.89309.f8
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin: A New HMG-CoA Reductase Inhibitor for the Treatment of Hypercholesterolemia

Abstract: Because of their excellent tolerability and their positive impact on lipid parameters, 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) have become the drugs of first choice for many patients with dyslipidemia. Rosuvastatin is an investigational statin in the U.S. with a number of favorable characteristics, which include low lipophilicity, high hepatocyte selectivity, minimal metabolism, and a low propensity for cytochrome P450 drug interactions. Rosuvastatin has been studied at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Atorvastatin has more powerful antiinflammatory and lipid-lowering effects than simvastatin, pravastatin, and lovastatin (13). However, rosuvastatin, a relatively new HMG-CoA reductase inhibitor, has a number of favorable characteristics, including low lipophilicity, high hepatocyte selectivity, minimal metabolism, and a low propensity for cytochrome P450 drug interactions (14). The present study comparing the two statins found both with favorable effects on lipid modulation, but 10 mg rosuvastatin in particular lowered serum TC and LDL-C levels to a greater extent in patients with hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 86%
“…Atorvastatin has more powerful antiinflammatory and lipid-lowering effects than simvastatin, pravastatin, and lovastatin (13). However, rosuvastatin, a relatively new HMG-CoA reductase inhibitor, has a number of favorable characteristics, including low lipophilicity, high hepatocyte selectivity, minimal metabolism, and a low propensity for cytochrome P450 drug interactions (14). The present study comparing the two statins found both with favorable effects on lipid modulation, but 10 mg rosuvastatin in particular lowered serum TC and LDL-C levels to a greater extent in patients with hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 86%
“…These agents lower lipid levels by inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, the rate-limiting enzyme in cholesterol synthesis, and are known to reduce cardiovascular morbidity and mortality in diabetic patients (13,14). Statins improve cardiovascular function in IR both indirectly via effects on blood elements such as triglycerides, cholesterol, and low-density lipoproteins (5,28) and by direct effects on the vasculature. These direct effects include the facilitation of endothelial nitric oxide (NO) production (12,16,41) and reduction of oxidative stress in the vessel wall (25,34,39).…”
mentioning
confidence: 99%
“…Specific non-lipid lowering effects of statins include antioxidant properties, maintenance of atherosclerotic plaque stabilization, antiinflammatory action, modulation of endothelial function, and anti-proliferation of VSMCs (Arnaboldi et al, 2007;Puccetti et al, 2007). Rosuvastatin, a relatively new HMG-CoA reductase inhibitor, has a lot of favorable characteristics, such as low lipophilicity, high hepatocyte selectivity, minimal metabolism, and a low propensity for cytochrome P450 drug interactions (Cheng-Lai, 2003). So, could the pleiotropic statin, rosuvastatin, reduce the homocysteine-induced excessive expression and activation of MMP-2 and abnormal cell migration of VSMCs?…”
Section: Introductionmentioning
confidence: 99%